The Buddy files : the case of the library monster - Butler, Dori Hillestad (Butler, Dori Hillestad. Buddy files, 2012)
Buddy is in the school library and kids are taking turns reading with him. While Buddy listens to a ghost story, he hears rustling in the shelves behind him. He turns to look, but doesn't see anyone back there. He hears a book fall. Something smells strange. Not human...not canine, not like anything Buddy has ever smelled before. Could it maybe be the school ghost Buddy has heard so much about? When the child he's sitting with leaves, Buddy goes over to the shelves to investigate...and comes face to face with a mysterious creature that has a long, blue tongue.